2006
DOI: 10.1002/hep.21330
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gene expression profiles between Opisthorchis viverrini and non‐Opisthorchis viverrini associated human intrahepatic cholangiocarcinoma†

Abstract: Intrahepatic cholangiocarcinoma (ICC) is the second most common primary cancer in the liver, and its incidence is highest in the northeastern part of Thailand. ICCs in this region are known to be associated with infection with liver flukes, particularly Opisthorchis viverrini (OV), as well as nitrosamines from food. To clarify molecular mechanisms of ICC associated with or without liver flukes, we analyzed gene expression profiles of OV-associated ICCs from 20 Thai patients and compared their profiles with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 47 publications
6
104
0
Order By: Relevance
“…Gene expression profile of 25 Japanese ICC patients (10 mass-forming, 2 periductal infiltrating, 11 mixed subtypes (mass-forming and periductal infiltrating) and 2 unknown subtype), using an in-house cDNA microarray demonstrated 52 up-regulated and 421 down-regulated genes (Obama et al, 2005). A comparison of global gene expression profiles of 20 Opisthochis viverrini-associated Thai ICC patients [10 mass-forming type and 10 mixed subtype (mass-forming and intraductal growth type)], with 20 Japanese ICC patients [8 mass-forming, 2 intraductal growth type and 10 mixed subtypes (mass-forming and intraductal growth type)], using an in-house cDNA microarray, indicated 77 up-regulated genes and 325 down-regulated genes in common (Jinawath et al, 2006). The current study of 15 Thai ICC patients (8 periductal infiltrating and 7 intraductal growing tissues) using Affymetrix GeneChip ® Human Exon 1.0ST identified 2,821 up-regulated and 1,361 down-regulated genes at the same fold change cut off (≥2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene expression profile of 25 Japanese ICC patients (10 mass-forming, 2 periductal infiltrating, 11 mixed subtypes (mass-forming and periductal infiltrating) and 2 unknown subtype), using an in-house cDNA microarray demonstrated 52 up-regulated and 421 down-regulated genes (Obama et al, 2005). A comparison of global gene expression profiles of 20 Opisthochis viverrini-associated Thai ICC patients [10 mass-forming type and 10 mixed subtype (mass-forming and intraductal growth type)], with 20 Japanese ICC patients [8 mass-forming, 2 intraductal growth type and 10 mixed subtypes (mass-forming and intraductal growth type)], using an in-house cDNA microarray, indicated 77 up-regulated genes and 325 down-regulated genes in common (Jinawath et al, 2006). The current study of 15 Thai ICC patients (8 periductal infiltrating and 7 intraductal growing tissues) using Affymetrix GeneChip ® Human Exon 1.0ST identified 2,821 up-regulated and 1,361 down-regulated genes at the same fold change cut off (≥2).…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanisms underlying this process remain unclear. Gene expression profiles using cDNA microarray have been generated, showing that O. viverrini associated ICC in Thai patients exhibited up-regulated of genes involve in xenobiotic metabolism whereas that in non O. viverrini associated ICC in Japanese patients presented enhanced gene expression in growth factor signaling pathway (Jinawath et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opisthorchis viverrini induced cholangiocarcinomas have been found to have different gene expression profiles to non-liver fluke related cholangiocarcinoma, with high expression of UGT2B11, UGT1A10, CHST4, SULT1C1 genes related to xenobiotic metabolism, whereas non-liver fluke related cholangiocarcinomas have upregulation of genes related to growth factor signalling (59) (63) . NFκB, a pivotal regulator of gene expression, is known to be specifically involved in the expression of genes of the UGT2B family (64) .…”
Section: Cholangiocarcinomamentioning
confidence: 99%
“…Some authors hypothesised that N-nitroso compounds are a primary carcinogen leading to CCA in humans in Northeastern Thailand (Migasena et al, 1980;Srisraluang & Boriboon, 1988). Jinawath et al showed the selective up-regulation of genes involved in xenobiotic metabolism in Thai patients with CCA, implying that these genes may be involved in the detoxification of possible carcinogens, such as nitrosamines (Jinawath et al, 2006). In hamster experimentally infected with O viverrini, CCA was induced by exposure to sub-carcinogenic doses of nitrosamine .…”
Section: Introductionmentioning
confidence: 99%